Accelerating gene function discovery by rapid phenotyping of fatty acid composition and oil content of single transgenic T(1) Arabidopsis and camelina seeds - Ma, Shijie (Plant Direct, 2020)
Arabidopsis is wildly used as a model plant and camelina is increasingly used for oilseed research and applications. Although the Arabidopsis genome has been sequenced for two decades, the functions of many lipid‐related genes and their regulators have not been well characterized. Improvements in the efficiency and accuracy of gene investigations are key to effective discovery of gene function and downstream bioengineering of plant oil quantity and quality. In this study, a visible marker was used to quickly identify transgenic T(1) seeds and a method has been developed to phenotype fatty acid compositions and oil content of single T(1) seeds. A whole seed direct transmethylation method was first optimized with multiple seeds and incubation at 85°C for 2 hours in a transmethylation solvent (5% H(2)SO(4) in methanol with 30% toluene cosolvent) is recommended. Based on this method, a single Arabidopsis seed mini‐transmethylation (SAST) method has been established in a 1.5 ml GC sample vial with 200 μl transmethylation solvent. Characteristics of the method were evaluated and it was used to phenotype transgenic T(1) seeds expressing AtFAD2 or RcWRI1. Our results indicate that fatty acid composition of T(1) individual seeds are consistent with those of pools of multiple seeds from higher generations. However, oil content per individual seed varied substantially and therefore pooling five seeds is recommended for phenotyping oil content of T(1) seeds. Additionally, a whole camelina single‐seed direct transmethylation was evaluated and results confirm its feasibility. The suitability of partial seed analysis of camelina was investigated but variation in composition of different seed tissues limits this approach.